Teenage mutant ninja turtles ([s.n.] : New Line Home Video, 1993)
When a magic scepter accidentlly transports April back through time 17th century Japan, the boys take off in hot pursuit, cowabungling their way out of the sewers right into Samurai-O-Rama. Now they must battle the evil Lord Norinaga to reclaim the magic scepter that will bring them back below the subways of New York City
Keywords: Samurai films; Motion pictures